The hidden connection between gut microbiota and periprosthetic joint infections: a scoping review - A. Singlitico; D. Grassa; R. Kaplan; A. Smimmo; G. Maccauro; R. Vitiello (Journal of Bone and Joint Infection)
Background: Periprosthetic joint infections (PJIs) pose a significant challenge in orthopedic surgery, and emerging evidence suggests that the gut microbiome may play a crucial role in their development and management. Despite the rarity of these infections, the continuous increase in prosthetic joint arthroplasties has made understanding how to prevent them more pressing. A stronger comprehension of the disruption of the gut microbiome and how this can lead to more of these infections and other pre-surgical risks may be crucial in preventing them. Objective: This article aims to provide a stronger understanding of the topic through the analysis of different pieces of already existing literature to help draw new conclusions and raise potential questions that need answering. Methods: A comprehensive search strategy without filters was employed, and multiple papers were thoroughly analyzed, understood, and compiled into this paper. Conclusions: Despite the limitations of some of the analyzed studies and finite evidence, this paper suggests that there could be a connection between periprosthetic joint infections and a compromised gut microbiome. However, further research is required to draw a definitive conclusion.